Knowledge of The Elderly Group of The Wreda Sejahtera Bali Foundation in Maintaining Dental and Oral Health - Yohanna Lily; I Gusti Agung Ayu Chandra Iswari Dewi; Ida Ayu Shinta Devi; Paskarani Mbiliyora; Kadek Putri Ariani; Luh Ketut Putri Setiari; Stivaldy Carisima Albertin Mullik (Interdental Jurnal Kedokteran Gigi (IJKG), 2025)
Introduction: Tooth loss conditions are one of the health problems in the oral cavity that can cause discomfort for sufferers because it interferes with daily activities, such as speaking, chewing, socializing, and self-confidence. Riskesdas in 2018, indicates that 58.7% of the Indonesian population aged 65 and above experience dental and oral problems, such as cavities, missing teeth due to extraction or spontaneous loss, filled teeth due to cavities, and loose teeth. To prevent dental diseases, especially in the elderly, one of the things that can be done is to provide oral health education to the elderly. Counseling activities play a crucial role in the prevention of dental and oral diseases. Methods: Observational study using a descriptive, cross-sectional design, both exposure and outcomes are measured simultaneously. The research method used is a lecture method for 35 minutes, followed by a demonstration on how to brush teeth and use dental floss for 10 minutes, and then concluded with a discussion session with the participants. The respondents are 28 individuals aged 55 years and above at the Wreda Sejahtera Foundation in Bali. Results and Discussion: Based on the distributed questionnaire, it was found that an average of 90.3% of the elderly answered the knowledge questions correctly. This result indicates that the participants were enthusiastic and paid close attention to the counseling material. Conclusion: The counseling activities carried out at the Wreda Sejahtera Bali Foundation were welcomed by the participants with enthusiasm in listening to the material and making the most of the question and answer session. This activity also has a positive impact on the elderly.